Beautiful creatures [videorecording (DVD)] - LaGravenese, Richard; Garcia, Kami; Ehrenreich, Alden, 1989-; Thompson, Emma; Irons, Jeremy, 1948-; Rossum, Emmy, 1986- (Alcon Entertainment : Distributed by Warner Home Video, 2013)
When newcomer Lena arrives in the small town of Gatlin she quickly captures the attention of Ethan, who only wants to escape what he views as a boring and dead end town. He quickly gets more than he bargained for. Together, they uncover dark secrets about their respective families, their history and their town.